Transverse Oscillations in a Coronal Loop Triggered by a Jet - Sarkar S.; Pant V.; Srivastava A.K.; Banerjee D. (My University, 2025)
We detect and analyse transverse oscillations in a coronal loop, lying at the south–east limb of the Sun as seen from the Atmospheric Imaging Assembly (AIA) onboard the Solar Dynamics Observatory (SDO). The jet is believed to trigger transverse oscillations in the coronal loop. The jet originates from a region close to the coronal loop on 19 September 2014 at 02:01:35 UT. The length of the loop is estimated to be between 377 – 539 Mm. Only one complete oscillation is detected with an average period of about 32±5min. Using magnetohydrodynamic (MHD) seismologic inversion techniques, we estimate the magnetic field inside the coronal loop to be between 2.68–4.5G. The velocity of the hot and cool components of the jet is estimated to be 168kms−1 and 43kms−1, respectively. The energy density of the jet is found to be greater than the energy density of the oscillating coronal loop. We therefore conclude that the jet triggered transverse oscillations in the coronal loop. To our knowledge, this is the first coronal loop seismology study using the properties of a jet propagation to trigger oscillations. © 2016, Springer Science+Business Media Dordrecht.